Research progress in the risk factors and screening assessment of dysphagia in the elderly - Chen, Kerong; Xing, Liwei; Xu, Bonan; Li, Yi; Liu, Tianyun; Zhang, Tingjuan; Shi, Hongping; Lu, Hanmei; Zhou, Wengang; Hou, Jianhong; Shi, Hongling; Qin, Dongdong (Frontiers in Medicine, 2022)
With the ageing of the population, the incidence of dysphagia has gradually increased and become a major clinical and public health issue. Early screening of dysphagia in high-risk populations is crucial to identify the risk factors of dysphagia and carry out effective interventions and health management in advance. In this study, the current epidemiology, hazards, risk factors, preventive and therapeutic measures of dysphagia were comprehensively reviewed, and a literature review of screening instruments commonly used globally was conducted, focusing on their intended populations, main indicators, descriptions and characteristics. According to analysis and research in the current study, previous studies of dysphagia were predominantly conducted in inpatients, and there are few investigations and screenings on the incidence and influencing factors of dysphagia in the community-dwelling elderly and of dysphagia developing in the natural ageing process. Moreover, there are no unified, simple, economical, practical, safe, and easy-to-administer screening tools and evaluation standards for dysphagia in the elderly. It is imperative to focus on dysphagia in the community-dwelling elderly, develop unified screening and assessment tools, and establish an early warning model of risks and a dietary structure model for dysphagia in the community-dwelling elderly.